A Viable Route for Lithium Ion Detection. Issue 3 (January 2014) - Gulino, Antonino; Lupo, Fabio; Cristaldi, Domenico A.; Pappalardo, Sebastiano; Capici, Calogero; Gattuso, Giuseppe; Notti, Anna; Parisi, Melchiorre F.
Abstract: Invited for the cover of this issue is the Gulino group at the University of Catania, Italy, with collaborators at the University of Messina. The cover image shows the mechanism of the reversible lithium‐sensing monolayer system. Abstract : Working on hybrid organic?inorganic materials suitable for the construction of photonic devices is a highly challenging interdisciplinary task... Read more about the story behind the cover in the Cover Profile and about the research itself onp. 442 ff .